Formation of n-nitrosamines in drinking water sources: Case studies from Western Australia - Linge, Kathryn; Kristiana, I.; Liew, D.; Nottle, C.; Heitz, A.; Joll, C. (American Water Works Association, 2017)
This study investigated the formation of eight N-nitrosamines after laboratory chlorination and chloramination of Western Australian source waters (from protected catchments), which experience periodic cyanobacterial blooms. All measured N-nitrosamines, except N-nitrosodipropylamine, were detected at least once, and total N-nitrosamine formation was higher after chloramination than after chlorination. While previous studies have shown that some cyanobacteria can be related to the formation of N-nitrosamines, formation of N-nitrosamines in the waters tested did not correlate with total cyanobacteria count. Estimates of toxicity, using published 50% lifetime excess cancer risk values, indicated that N-nitrosodimethylamine (NDMA) was the highest contributor to the total measured N-nitrosamine toxicity, suggesting that other measuredN-nitrosamines will only influence toxicity when they arepresent at significantly higher concentrations than NDMA.When assessing the overall health impact of disinfectionby-products, it is important to also consider the formationof disinfection by-products other than N-nitrosamines,which may be present at higher concentrations and thus maypresent higher toxicity.